1973
DOI: 10.1007/bf00162539
|View full text |Cite
|
Sign up to set email alerts
|

The laboratory aims questionnaire?A new method for course improvement?

Abstract: A simple method of diagnosing areas for course improvement in university science and engineering laboratory courses is described. A first year physics laboratory course is examined in terms of a set of aims. A questionnaire was used for staff and students to rate the importance of these aims in the cases (i) of each group's conception of what an ideal course in the subjec t should be, and (ii) each group's rating of the "traditional" and "non-traditional" components of the particular course under investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Based on literature [7][8][9][10] and existing lab manuals, a survey on lab goals for an electronics lab was developed. The survey consists of a list of 17 goals to be scored on a five-point Likert scale (very important to not important) and an explicit question to add extra goals if needed.…”
Section: Surveymentioning
confidence: 99%
“…Based on literature [7][8][9][10] and existing lab manuals, a survey on lab goals for an electronics lab was developed. The survey consists of a list of 17 goals to be scored on a five-point Likert scale (very important to not important) and an explicit question to add extra goals if needed.…”
Section: Surveymentioning
confidence: 99%
“…The importance of manipulative skills continues to have an important role in chemical education. In subsequent articles and books, authors have made it clear that the development of these skills is a worthy goal for students to attain by including it on numerous lists of educational outcomes for laboratory work (American Association for the Advancement of Science, 1993;Anderson, 1976;Biddle & Bush, 1949;Boud, 1973;Hegarty-Hazel, 1990;Klopfer, 1971;National Association of Secondary-School Principals, 1953;National Research Council, 1996;Pella, 1961;Shulman & Tamir, 1973;Sund & Trowbridge, 1967).…”
Section: A Significant Object Of Discoursementioning
confidence: 99%
“…Following this year a research project by Boud (1973) looked at the aims of the course as seen in retrospect by staff and students. The results of the project gave a working list of aims appropriate in general to an introductory physics' laboratory course and additionally indicated that as far as the students were concerned the four-hour experiments that were traditional for such an introductory course were not as effective as the new style, ie, short single-concept experiments in fulfilling these aims.…”
Section: Year Twomentioning
confidence: 99%
“…Incorporated in the redesigning of the course were the findings of the aims evaluation (Boud, 1973) following Year Two, a post-course questionnaire, and feedback from individual experiments. Choice of experiments was free and informed but pacing was introduced by individual timetables.…”
Section: Built-in Feedbackmentioning
confidence: 99%
See 1 more Smart Citation